The Secret History of the Soul : Physiology, Magic and Spirit Forces from Homer to St Paul. - Sugg, Richard, 1969- (Cambridge Scholars Publishing, 2013)
What would Christianity be like without the soul? While most people would expect the Christian bible to reveal a highly traditional opposition of matter and spirit, the spirit forces of the Old and New Testaments are often surprisingly physical, dynamic, and practical, a matter of energy as much as ethics. The Secret History of the Soul examines the forgotten or suppressed models of body, soul, and human consciousness found in the literature, philosophy and scripture of the ancient and classi ...